HUBUNGAN PHBS DAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING PADA ANAK DI WILAYAH KERJA PUSKESMAS KEDAUNG BARAT KABUPATEN TANGERANG 2021 - Aisah Handika; Siti Rochmani (Nusantara Hasana Journal, 2022)
In building quality human resources, health in the community is one of the important pillars. However, the problem of stunting is still a nutritional problem that occurs in the community, especially in Indonesia based on WHO in Southeast Asia, Indonesia is included in the third country with a high percentage of stunting. Stunting is a condition where a person's height is lower than a group of people of the same age. Inhibition in cognitive and psychomotor, degenerative diseases, difficulties in learning and achievement, and being a low-quality human resource, are some of the bad effects of stunting. Children are the nation's assets in the future. If the state of human resources in Indonesia suffers from stunting, what will happen is that it is difficult for Indonesia to compete globally. This study aims to determine the relationship between PHBS and exclusive breastfeeding with the incidence of stunting in toddlers in the working area of ​​the Kedaung Barat Health Center, Tangerang Regency. Methods This research uses quantitative, with a case control or case control design with a retrospective approach. The sample was taken through purposive sampling technique with the number of samples being 150 respondents from parents who had stunting children (cases) as many as 75 and normal children (controls) as many as 75. The results of bivariate analysis using the chi square test between PHBS and stunting were obtained "p value" i.e. 0.008 where “p value” <0.05. The results between exclusive breastfeeding and the incidence of stunting obtained "p value" which is 0.000 where "p value" <0.05. The conclusion of this study is that there is a significant relationship between PHBS and exclusive breastfeeding with the incidence of stunting in children under five in the working area of ​​the Kedaung Barat Health Center, Tangerang Regency.